The Shelter Band: Homelessness, social support and self-esteem in a community music partnership. Issue 2 (1st August 2019) - Knapp, David H.; Silva, Carlos
The transition from homelessness into mainstream society involves external factors, such as obtaining housing and employment. Research also indicates that social support and perceptions of self-efficacy are important psychological factors in escaping homelessness. Music interventions, such as participation in performing ensembles, have been shown to aid in the development of social skills among marginalized populations and improve participants' psychological well-being. The purpose of this study was to explore the effects of a music intervention on perceptions of social support and self-esteem among individuals experiencing homelessness. Members of The Shelter Band included residents at a large emergency homeless shelter in the Southeast United States, shelter staff and university music education students. The band rehearsed a variety of rock songs weekly and performed regularly for civic events. Researchers investigated the effects of band participation on perceptions of social support and self-efficacy using a mixed-method approach. Qualitative data were obtained over a three-year period through interviews with band members, shelter staff and the participant researchers. These data were transcribed and analysed for themes according to a priori and in vivo codes by the participant researchers. Social support and self-esteem were also specifically investigated by comparing differences in responses to the Interpersonal Support Evaluation List (ISEL) between band members and non-member shelter residents. Qualitative data indicated that participants in The Shelter Band demonstrated improved perceptions of social support and self-esteem. In a few cases, participation in the band was identified as a key factor in individuals escaping decades-long chronic homelessness. Other themes emerged from participants, including reduced recidivism and improved case management. Quantitative data of perceptions of social support and self-esteem between Shelter Band members and non-member residents of The Shelter revealed no statistically significant results. As music educators continue to explore opportunities for their work, it is useful to consider collaborations with community partners. By involving shelter staff in The Shelter Band, staff and music educators were able to direct the intervention towards individuals' needs. These collaborations can be beneficial for both the university and community partners. In addition, possibilities for this kind of socially responsive pedagogy in music teacher training are discussed.